DECONSTRUCTING NORMS: AN EXAMINATION OF GENDERED LANGUAGE IN BOY ABUNDA’S WHY CAN’T WE HAVE A GAY PRESIDENT? - Morata, Trixia Kate; Embalzado, Charlyn Mae; Mediado, Francel; Panganoron, Lyndelie; Samantela, Josef Jude; Santiano, Hanna Maria; Villa, Wenalyn; Villaflor, Jannah Veronica; Fajardo, Dan Fereth (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2026)
This study examines the speech content of Boy Abunda's Why Can't We Have a Gay President using the Model of Feminist Theory according to Jo Ann Arinder. To investigate traditional gender norms and expectations, the study looks at the language used by Boy Abunda in his speech,